SCHOOL LITERACY MOVEMENT TROUGH THE CLASSROOM READING CORNER AT INPRES ELEMENTARY SCHOOL TOMBOLO, TOMBOLOPAO DISTRICT, GOWA REGENCY - Zukhraeni Zukhraeni; Erwin Akib; Munirah Munirah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This study aimed to determine the implementation of the School Literacy Movement at the habituation stage, the development stage, and the learning stage through the classroom reading corner at Inpres Elementary school Tombolo, the supporting and inhibiting factors for the use of the classroom reading corner in the implementation of the School Literacy Movement at Inpres elementary School Tombolo. This research was a qualitative research. The study was conducted at Inpres elemtary School Tombolo, Tombolopao District, Gowa Regency. There were 12 informans in this study consisting of the principal, 5 class teachers, 1 librarian, 5 student representatives from each grade level. Data were collected through direch observasition at the Education Unit, in-depth interviews with informants, and documentation of activitees as well as administrative completeness of the implementation of the School Literacy Movement.The results showed that the implementation of the School Literacy Movement at Inpres Elemtary School Tombolo, had been carried out well starting from the Habituation Stage, Development State, and Learning State by utilizing the classroom reading corner, in general, two reading strategies are used, namely silent and loud. The implementation of the School Literacy Movement continues in several classes during the learning period from home deu to the C.19 pandemic by utilizing digital platforms. Sources of reading materials only use the classroom reading corner and school library in the implementation of the School Literacy Movement.